The 12/02/2007 SW Cape San Vicente Earthquake: SFS (San Fernando SP) and WM (Western Mediterranean) networks preliminary report - Martín-Davila, J. (2006)
The western part of the Eurasia-Africa plate boundary crosses the Gulf of Cadiz at about 36oN latitude, without a well defined boundary line. The plate convergence, at a rate of a few mm/year in a NNW/SSE to NW/SE direction (Buforn et al 2004), induces a moderate magnitude and shallow depth seismicity, but a clear intermediate activity (figure 1) is also present at the area and large magnitude historical events have been documented since the roman times (Martin- Davila and Pazos, 2003), among them the 1755 Lisbon earthquake, with an estimated magnitude of 9.0. This event, with an epicentre located SW of Cape San Vicente, caused around 20000 casualties. More recently, on February 28, 1969, an 8.1 magnitude event was located in the same area. Both shocks induced a tsunami, with a measured wave height at Cadiz Bay of about ten meters for the 1755 event and one meter for the 1969.